2019
DOI: 10.1123/japa.2017-0396
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Activity Governmental Programs on Health Status in Independent Older Adults: A Systematic Review

Abstract: This systematic review analyzes the evidence of the effects of physical activity governmental programs oriented toward the health of independent older adults. Medline, Web of Science, PsycINFO, and Psychology & Behavioral Sciences Collection databases were used for data mining, and the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols recommendations were followed. Five studies (n = 2,545 participants) fulfilled the established inclusion criteria. The physical activity programs had be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
44
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 64 publications
1
44
0
3
Order By: Relevance
“…Moreover, in many studies, this percentage was higher in the study group than in the control group; therefore, the result of fewer falls and fallers at follow-up in the study group acquires even more significance in light of these considerations. Valdés-Badilla et al [55] reported the beneficial effects on quality of life, fall risk, activities of daily living, physical activity levels, and blood parameters of governmental physical activity programs for independent older adults. Finally, Tricco et al [56] demonstrated that exercise was associated with a lower risk of injurious falls compared with usual care, but the type of physical activity used to reduce falls should be selected on the basis of patient and caregiver values.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in many studies, this percentage was higher in the study group than in the control group; therefore, the result of fewer falls and fallers at follow-up in the study group acquires even more significance in light of these considerations. Valdés-Badilla et al [55] reported the beneficial effects on quality of life, fall risk, activities of daily living, physical activity levels, and blood parameters of governmental physical activity programs for independent older adults. Finally, Tricco et al [56] demonstrated that exercise was associated with a lower risk of injurious falls compared with usual care, but the type of physical activity used to reduce falls should be selected on the basis of patient and caregiver values.…”
Section: Discussionmentioning
confidence: 99%
“…En este contexto, se ha informado que el entrenamiento de resistencia produce mejoras sobre el flujo sanguíneo en hombres y mujeres de mediana edad, sin embargo, se desconoce si los efectos vasculares son similares en los AM (Egana, Reilly, & Green, 2010). Por otra parte, se ha reportado que intervenciones con actividad física que incorporan entrenamiento de fuerza muscular y resistencia aeróbica son claves para el mantenimiento y mejora de la salud cardiovascular y metabólica en los AM (Valdés-Badilla et al, 2019), hecho que reforzaría los resultados encontrados en nuestra investigación que desarrollo un protocolo de entrenamiento basado en la resistencia muscular.…”
Section: Discussionunclassified
“…Los cambios en la capacidad de equilibrio en respuesta a los aumentos de fuerza exhibidos por los AM, posiblemente se deban a un mayor desarrollo de las tasas de torque causadas por una mayor área de la seccioìn transversal de las fibras tipo II (Pavol et al, 2002). Hechos favorables, debido a que el equilibrio dinámico es una actividad compleja que involucra grandes grupos musculares, coordinación y función sensorial (Padilla Colón et al, 2014) y se relaciona con un menor riesgo de caídas en los AM (Valdés-Badilla et al, 2019).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…It seems clear the importance of promoting the practice of regular physical activity at all times of life, not only due to its impact on the level of physical health [ 16 , 17 , 18 ] but also on the mental health of citizens. In moments of great psychological and emotional fragility such as the ones we live in, its practice gains even more importance [ 19 ].…”
mentioning
confidence: 99%